An experimental study into the chemical effects of direct gasoline injection into retained residuals in a homogeneous charge compression ignition engine. (December 2016) - Hunicz, Jacek
Fuel injection into retained residuals and the resulting exhaust-fuel reactions appear to be an effective method for enhancing mixture reactivity in residual effected homogeneous charge compression ignition engines. Varying the extent of reactions preceding the main combustion event enables the control of auto-ignition timing and heat release. Although fuel injection during the negative valve overlap period is widely utilised, there is still insufficient amount of data on its chemical effects. This study experimentally explores the species formation as a result of negative valve overlap exhaust-fuel reactions. To collect experimental data, a single-cylinder engine with negative valve overlap and direct gasoline injection was utilised. Valving strategy of the engine was strategically set to achieve a high rate of backflows at the end of the intake process. Negative valve overlap gas, diluted by intake air, was sampled from the intake runner and passed to a Fourier transform infrared analytical system. A dedicated procedure was applied to compute degrees of fuel conversion into species from the diluted samples. The experiments were designed to acquire comprehensive data on the effects of different fuel injection timings on species formation during negative valve overlap. The results showed that exhaust-fuel reactions could produce high quantities of methane and light unsaturated hydrocarbons. At early negative valve overlap fuel injection, up to 25% of fuel was converted into species, whereas chemical changes were negligible for late fuel injection. Additionally, the effects of excess air and amounts of fuel injected during negative valve overlap were investigated.